PROXIMATE COMPOSITION OF Reinwardtiodendron humile (Hassk.) Mabb. FRUIT FROM BOGOR BOTANIC GARDENS COLLECTION - Saniyatun Mar'atus Solihah; Inggit Puji Astuti (BIOMA : JURNAL BIOLOGI MAKASSAR, 2022)
Abstract Reinwardtiodendron humile (Hassk.) Mabb. is one of the members of the Meliaceae tribe with the potential to be developed and consumed as fresh fruit or processed fruit. This research aims to determine the proximate composition or nutritional values contained in R. humile. Proximate analysis of R. humile included analytical determinations of water, ash, crude fat, protein, crude fibre, and carbohydrates. All tests for each of the parameters or components were carried out two times. Then, the contents determined through proximate tests were calculated using certain formulas. The results of this study indicate that the proximate composition of R. humile consisted of water, ash, fat, protein, crude fibre, and carbohydrates (74.2% - 75.28%; 1.35% - 1.54%; 0.53% - 0.72%; 2.48% - 2.73%; 0.86% - 3, 47%; and 16.7% - 20.14%). These results meant the fruit contents met the quality standards of fruit, except for the protein content. The results of the analysis of the proximate composition also show that the nutritional values of R. humile fruit did not significantly differ from the nutritional values of other fruits of the Meliaceae tribe commonly consumed by humans, such as duku, langsat, and kokosan. Keywords: fruit, nutritional value, proximate analysis, Reinwardtiodendron humile